Long-term cosmetic outcome after preoperative radio-/chemotherapy in locally advanced breast cancer patients Langfristiges kosmetisches Ergebnis nach neoadjuvanter Radio‑/Chemotherapie bei lokal fortgeschrittenen Brustkrebspatientinnen - Matuschek, Christiane; Nestle-Kraemling, Carolin; Haussmann, Jan; Bölke, Edwin; Wollandt, Sylvia; Speer, Vanessa; Djiepmo Njanang, Freddy Joel; Tamaskovics, Bálint; Gerber, Peter Arne; Orth, Klaus; Ruckhaeberle, Eugen; Fehm, Tanja; et al. (Strahlentherapie und Onkologie, 2019)
Background: Preoperative radiotherapy and chemoradiotherapy (PRT/PCRT) represent an increasingly used clinical strategy in different tumor sites. We have previously reported on a PRT/PRCT protocol in patients with locally advanced non-inflammatory breast cancer (LABC) with promising clinical results. However, concerns regarding a possible unfavorable influence on cosmesis still exist. Thus, the aim of the current study was to examine long-term cosmetic outcome in our series of LABC patients treated with PRT/PCRT followed by breast-conserving surgery (BCS) or mastectomy (ME). Patients and methods: Of the 315 patients treated with PRT/PCRT in the years 1991 to 1999, 203 were still alive at long-term follow-up of mean 17.7 years (range 14–21). Thirty-seven patients were lost to follow-up and 58 patients refused to be contacted, which resulted in 107 patients (64 patients after BCS and 43 after mastectomy) being available and willing to undergo further cosmetic assessment. One patient had a complete response after PRT/PCRT and refused surgery. PRT/PCRT consisted of external beam radiation therapy (EBRT) with 50 Gy (5 × 2 Gy/week) to the breast and the supra-/infraclavicular lymph nodes combined with a consecutive electron boost or (in case of BCS) a 10-Gy interstitial brachytherapy boost with Ir-192 prior to EBRT. Overall, chemotherapy was administered either prior to RT or concomitantly in the majority of patients. BCS and mastectomy were performed with and without reconstruction. The cosmetic outcome was assessed by patient questionnaire, panel evaluation, and breast retraction assessment (BRA) score. Results: Eighty percent of all BCS patients rated their overall cosmetic result as “excellent” or “good” as compared to 55.8% after mastectomy. Patient and panel ratings on cosmetic outcomes were similar between the two groups. No grade III or IV fibrosis were detected in any of the groups. The median BRA score after breast conserving surgery was 2.9. Conclusion: PRT/PCRT is associated with low grades of fibrosis and a good to excellent long-term cosmetic outcome.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Breast conserving surgery; Cosmesis; Mastectomy; Panel rating; Patient rating